Personalised pathway analysis reveals association between DNA repair pathway dysregulation and chromosomal instability in sporadic breast cancer. Issue 1 (26th September 2015) - Liu, Chao; Srihari, Sriganesh; Lal, Samir; Gautier, Benoît; Simpson, Peter T.; Khanna, Kum Kum; Ragan, Mark A.; Lê Cao, Kim-Anh
Abstract : The Homologous Recombination (HR) pathway is crucial for the repair of DNA double‐strand breaks (DSBs) generated during DNA replication. Defects in HR repair have been linked to the initiation and development of a wide variety of human malignancies, and exploited in chemical, radiological and targeted therapies. In this study, we performed a personalised pathway analysis independently for four large sporadic breast cancer cohorts to investigate the status of HR pathway dysregulation in individual sporadic breast tumours, its association with HR repair deficiency and its impact on tumour characteristics. Specifically, we first manually curated a list of HR genes according to our recent review on this pathway (Liu et al., 2014), and then applied a personalised pathway analysis method named Pathifier (Drier et al., 2013) on the expression levels of the curated genes to obtain an HR score quantifying HR pathway dysregulation in individual tumours. Based on the score, we observed a great diversity in HR dysregulation between and within gene expression‐based breast cancer subtypes, and by using two published HR‐defect signatures, we found HR pathway dysregulation reflects HR repair deficiency. Furthermore, we identified a novel association between HR pathway dysregulation and chromosomal instability (CIN) in sporadic breast cancer. Although CIN has long been considered as a hallmark of most solid tumours, with recent extensive studies highlighting its importance in tumour evolution and drug resistance, the molecular basis of CIN in sporadic cancers remains poorly understood. Our results imply that HR pathway dysregulation might contribute to CIN in sporadic breast cancer. Highlights: Homologous recombination (HR) pathway dysregulation is quantified at tumour level. HR dysregulation is indicative of HR repair deficiency. An association between HR dysregulation and chromosomal instability is uncovered. The results are reproducible across four large breast cancer cohorts.